Predictors of readiness for oral rapid HIV testing by Chilean health care providers - Lisette P. Irarrázabal; Judith A. Levy; Kathleen F. Norr; Rosina Cianelli; L. Michele Issel; Carlos M. Pérez; Anna Hotton
ABSTRACT Objective This study identified the personal characteristics that affect Chilean health care providers' readiness to adopt HIV Oral Rapid Testing (ORT) in Chile as a new clinical evidence-based practice (EBP). Methods Using a cross-sectional research design, the study sampled 150 nurses, midwives, and physicians employed at four clinics within the Pontifícia Universidad Católica de Chile Health Network in Santiago. Participants completed a self-administered survey asking about their demographic background, EBP attitudes and experience, personal beliefs related to HIV, the importance of HIV testing, and perceived self-comfort in performing a rapid HIV test. Results Of the participants, 90% believed that incorporating ORT would make a positive difference in their practice and said that they would be willing to adopt the technology for that reason. Nonetheless, the providers reported a mean "readiness to implement ORT" score of 15.1 out of a possible value of 20, suggesting only moderate self-perceived readiness to adopt the EBP. Education, beliefs about evidence-based practice, perceived comfort in performing ORT, and perceived importance of HIV testing explained 43.6% of the variance in readiness to adopt ORT. Conclusion The findings of this first ORT pre-implementation study in Chile can help guide policy makers and HIV stakeholders to prepare for and increase primary health care providers' readiness to successfully adopt this evidence-based technology. Successful adoption of ORT could increase Chile's capacity to reach HIV-vulnerable Chileans for testing and referral to care if infected, thus helping the country to reduce further transmission of the virus and its medical complications.